Rotordynamics of Turbine Labyrinth Seals with Rotor Axial Shifting - Jinxiang Xi; David L. Rhode (International Journal of Rotating Machinery)
Rotors in high-performance steam turbines experience a significant axial shifting during starting and stopping processes due to thermal expansion, for example. This axial shifting could significantly alter the flow pattern and the flow-induced rotordynamic forces in labyrinth seals, which in turn, can considerably affect the rotor-seal system performance. This paper investigates the influence of the rotor axial shifting on leakage rate as well as rotordynamic forces in high-low labyrinth seals over a range of seal clearances and inlet swirl velocities. A well-established CFD-perturbation model was employed to predict the rotordynamic coefficients. A surprisingly large effect was detected for rotordynamic characteristics due to rotor shifting. It was also found that a less destabilizing effect arose from rotor axial shifting in the leakage flow direction, whereas a more destabilizing effect arose from shifting against the leakage flow direction. Further, a tentative explanation was proposed for the large sensitivities of dynamic forces to rotor axial shifting.